Multilevel analysis of factors associated with perinatal intimate partner violence among postpartum population in Southern Ethiopia - Tafesse Lamaro Abota; Fikre Enqueselassie Gashe; Negussie Deyessa (Scientific Reports, 2022)
Abstract Violence around pregnancy is critical in nature and major public health problem worldwide. Thus, the present study aims to determine the extent of perinatal partner violence and to identify its individual and community-level factors among postpartum women in Southern Ethiopia. A total of 1342 postpartum women nested in 38 ‘Kebles’ (clusters) were enumerated using multistage-clustered sampling techniques for multilevel analysis. Different parameters were computed for model comparison and model fitness. The overall prevalence of intimate partner violence before, during, and/or after pregnancy was estimated to be 39.9% [95% CI 36.9–44.5]. About 18% of women reported continuous abuse over the perinatal period. Postpartum women who live in rural areas [adjusted odds ratio (AOR) = 2.46; 95% CI 1.21–5.01], or in neighborhoods with high IPV favoring norms [AOR = 1.49; 95%CI 1.01–2.20], high female literacy [AOR = 2.84; 95%CI 1.62–5.01], high female autonomy [AOR = 2.06; 95%CI 1.36–3.12], or in neighborhoods with lower wealth status [AOR = 1.74; 95%CI 1.14–2.66] were more likely to encounter PIPV. The complex patterns of interplaying factors operating at different levels could put pregnant or postpartum women at higher risk of IPV victimization. Therefore, policies that prioritize the improvement of contextual factors, particularly norms toward IPV and women’s empowerment are likely to be the most effective interventions.